The Analysis Of Tax Saving Management Implementation (Case Study Of Company X) - Rian Yuli Sugesti; Jaka Isgiyarta (Green Publisher Indonesia, 2025)
This study aims to determine the tax management applied to obtain tax savings at PT. X. The research method used is descriptive qualitative research. The type of data in this study was obtained from primary data, where researchers conducted research directly in the field with interview techniques with resource persons, observation and documentation and secondary data taken from literature studies. The results of this study indicate that has implemented tax management properly and correctly in accordance with applicable tax regulations. The company uses several strategies or steps in implementing tax management, so that the company obtains tax savings.